Проекты экономического освоения Закавказья (1826—1834) - В. Г. Тунян (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Անդրկովկասի տնտեսական յուրացման հարցում գոյություն ուներ երկու մոտեցում՝ ինքնակալության կողմից երկրամասի գաղութացման և երկրորդ բուրժուական սոցիալ-տնտեսական հարաբերությունների զարգացման ուղիով։ There existed two approaches to the question of economic appropriation of Transcaucasia: colonization of the territory by the tsarist autocracy -and second through the development of bourgeois social economic relations.
Keywords: History; Political Science; Modern History; Economic History and Conditions; D History; H Social Sciences; J Political Science